1988
DOI: 10.1161/01.hyp.11.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Functional versus structural changes of forearm vascular resistance in hypertension.

Abstract: SUMMARY Structural changes in resistance vessels have been considered an important factor in triggering and maintaining chronic hypertension in humans and in experimental animals. To determine whether the increased forearm vascular resistance observed following vasodilator maneuvers in hypertensive patients is predominantly due to structural or to functional changes, we examined the influence of different vasodilator stimuli on forearm blood flow and blood pressure in 22 male patients with established essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
1

Year Published

1988
1988
1991
1991

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
(25 reference statements)
2
18
1
Order By: Relevance
“…First, the procedures used in our study were really able to induce complete vascular relaxation. Second, as this was the case in Schulte et al's study 1 only after the addition of nifedipine, they evidently did not push the ischemia-exerciseheating procedures for vasodilatation quite as far as we did in our study.…”
contrasting
confidence: 48%
See 2 more Smart Citations
“…First, the procedures used in our study were really able to induce complete vascular relaxation. Second, as this was the case in Schulte et al's study 1 only after the addition of nifedipine, they evidently did not push the ischemia-exerciseheating procedures for vasodilatation quite as far as we did in our study.…”
contrasting
confidence: 48%
“…The addition of nifedipine increased blood flow up to 30% in both their normotensive and hypertensive subjects and resulted in R^,, values that were apparently lower than those reached in our study. Schulte et al 1 therefore concluded that 1) complete vascular relaxation was only achieved when calcium channel blockers were added, and 2) R^,, was not significantly elevated in their hypertensive group. On closer scrutiny, however, their results seem to confirm the results of our group.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1 questioned some of the methods used in our study 2 and cast doubts on our conclusions. We will comment here on the methodology only and leave it to the reader to draw conclusions from the data published.…”
Section: Professor Folkowmentioning
confidence: 76%
“…Statistical analysis. As detailed in our study, 2 we have chosen a univariate approach by comparison of carefully selected matched pairs, which is recognized as a valid method of analyzing such data. When we analyzed our data as suggested by Folkow, 1 although resting blood pressure values did not form a continuum, we obtained a weak but significant correlation between mean arterial pressure and resistance at maximal dilation (r=0.363; p<0.05).…”
Section: Professor Folkowmentioning
confidence: 99%